2007
DOI: 10.1002/nau.20384
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of filling related sensation between anorectum and lower urinary tract and its impact on the sequence of their evacuation. A study in healthy volunteers

Abstract: When the bladder is full, sensation of rectal filling is decreased. When healthy people visit the toilet to defecate, the initiation of micturition often precedes that of defecation, even if both organs are considered equally full.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 21 publications
1
24
0
1
Order By: Relevance
“…A close relationship between bladder function and intestinal function has been demonstrated in various animal models [9, 10] and in clinical studies [11, 12]. A urodynamic study by De Wachter et al showed that rectal distention significantly influences the sensation of bladder filling [13], while Panayi et al detected detrusor overactivity when the rectum was distended and not when it was empty [12]. Crosstalk between bladder and bowel might occur via overlapping neural pathways, including the dorsal root ganglia and spinal cord, and via shared neurotransmitters [14].…”
Section: Introductionmentioning
confidence: 99%
“…A close relationship between bladder function and intestinal function has been demonstrated in various animal models [9, 10] and in clinical studies [11, 12]. A urodynamic study by De Wachter et al showed that rectal distention significantly influences the sensation of bladder filling [13], while Panayi et al detected detrusor overactivity when the rectum was distended and not when it was empty [12]. Crosstalk between bladder and bowel might occur via overlapping neural pathways, including the dorsal root ganglia and spinal cord, and via shared neurotransmitters [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the peripheral nervous system, the same nerves innervate the bladder and the anal rectum. In the central nervous system (CNS), afferent nerve signals from these organs are processed in the same regions of the brain, and both bladder and bowel functions are controlled by the same supraspinal regions such as the anterior cingulate gyrus, the insular cortex and the prefrontal cortex region of the brain [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…In animal experiments, both in vivo and in vitro , bladder‐to‐rectum and rectum‐to‐bladder reflexes were examined in healthy rats and pathological animal models . Furthermore, previous clinical studies showed that constipation alters bladder sensation, and simultaneous management of constipation and LUTS are recommended . Taken together, these observations show that the conditions of the rectum and bladder influence each other, and management of rectal conditions is also important for LUTS/OAB patients in Western medicine …”
Section: Clinical Concept Of General Kampo Medicinementioning
confidence: 95%